Heteromerization Modulates mu Opioid Receptor Functional Properties in vivo - Ugur, Muzeyyen; Derouiche, Lyes; Massotte, Dominique (Frontiers in Pharmacology, 2018)
Mu opioid receptors modulate a large number of physiological functions. They are in particular involved in the control of pain perception and reward properties. They are also the primary molecular target of opioid drugs and mediate their beneficial analgesic effects, euphoric properties as well as negative side effects such as tolerance and physical dependence. Importantly, mu opioid receptors can physically associate with another receptor to form a novel entity called heteromer that exhibits specific ligand binding, signalling and trafficking properties. As reviewed here, in vivo physical proximity has now been evidenced for several receptor pairs, subsequent impact of heteromerization on native mu opioid receptor signalling and trafficking identified and a link to behavioural changes established. Selective targeting of heteromers as a tool to modulate mu opioid receptor activity is therefore attracting growing interest and raises hopes for innovative therapeutic strategies.